Analisis Pemanfaatan Macromedia Flash 8 sebagai Upaya Pengembangan Media Pembelajaran Tematik Terpadu di Sekolah Dasar - Titik Setyaningsih; Farida S (Universitas Negeri Padang, 2022)
The 2013 curriculum which applies to elementary school education, is a curriculum that emphasizes integrated thematic learning from class I level to class VI. It is integrated thematic learning then combined with a saintifical approach. Merging integrated thematic learning with a saintifical approach should provide students with a meaningful learning experience through the full delivery of learning materials without feeling a barrier between matter one to the other through scientific learning activities. But in reality, the process of corresponding learning is still hinted at by the inadequate use of the learning media for unified thematic learning. Thus, there is a learning medium that can convey a unified, comprehensive, unified thematic learning material that is needed. To that end, this research aims to review the Macromedia Flash 8 development of integrated thematic study-based Macromedia Flash 8 at elementary school. The method of this research used is the literature study obtained through searches of relevant journal articles, books, and other scientific sources. Analysed studies have proved that the unified thematic media based Macromedia Flash 8 is characterized by quality, fun, effective, and practical learning media.